2019
DOI: 10.1017/s1742170519000309
|View full text |Cite
|
Sign up to set email alerts
|

Short food supply chains: the link between participation and farmers' competencies

Abstract: Research on short food supply chains (SFSCs) has experienced a remarkable growth during recent years, offering ample evidence that the creation of such alternative food distribution networks can bring multiple benefits to both farmers and consumers. Nevertheless, farmers' engagement in SFSCs is still limited in many countries. Two studies designed to illustrate the role of competencies in the development of SFSCs are reported in this paper. The first one assessed the influence of farmers' self-perceived compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 86 publications
0
39
0
Order By: Relevance
“…Moreover, the empirical evidence of the return on investment for CSA is quite limited. The ambiguous effect of economic sustainability was also confirmed by Charatsari et al (2020). During a comparative study, they invited 33 farmers to participate in SFSCs and 38 farmers involved in the conventional food system in Greece.…”
Section: Short Food Supply Chains (Sfscs) and Sustainabilitymentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the empirical evidence of the return on investment for CSA is quite limited. The ambiguous effect of economic sustainability was also confirmed by Charatsari et al (2020). During a comparative study, they invited 33 farmers to participate in SFSCs and 38 farmers involved in the conventional food system in Greece.…”
Section: Short Food Supply Chains (Sfscs) and Sustainabilitymentioning
confidence: 94%
“…Meanwhile, studies investigating CSA found the economic benefits of SFSCs are less evident (Janssen 2010;Balázs et al 2016). As concluded by Charatsari et al (2020), the potential economic benefits of participating in SFSCs tend not to be the main motivation of their participation. However, findings from this study suggest that the economic pillar is the most prominent motivating factor among the respondents.…”
Section: Hypothesis Evaluation -Five Dimensions Of Sustainabilitymentioning
confidence: 99%
“…In addition to the scholars working within the Wageningen school, researchers on AFNs have extensively documented the significance of farmer values, knowledge and practices in AFNs (Andreatta 2000;Best 2008;Charatsari et al 2019;Darnhofer et al 2005;Zagata 2010). While qualitatively analyzing alternative farming styles yields valuable descriptive information on the livelihoods of producers in AFNs, it does not help explain what has caused the crisis of the corporate farming and entrepreneurial farming styles, nor does it provide a framework to analyze more systemic processes, such as the conventionalization of the organic farming sector (Best 2008;Buck et al 1997).…”
Section: Farming Differentlymentioning
confidence: 99%
“…In Slovakia, sales in short supply chains are estimated at 3% and the ambitious government target of increasing it to 7% by the end of 2020 (Floriš et al, 2018). In Greece, studies by C. Charatsari et al (2019) showed that only around 14,000 growers sell their produce at marketplaces, which is only 0.02% of the total farmer population in Greece. Whereas in the Province of Malaga in Spain, T. Rucabado-Palomar et al (2020) defined the share of farmers in short supply chains as less than 2%.…”
Section: Resultsmentioning
confidence: 99%